TOLERANSI KEAGAMAAN MASYARAKAT DI DESA GUWA LOR KECAMATAN KALIWEDI KABUPATEN CIREBON - Akhsin Ridho (Harmoni, 2020)
The study, which begins with the existence of differences in religious rituals in rural areas, a tradition that is maintained from time to time, is tolerant, religious, and inclusive aims to determine the process of forming harmony in different communities in religious understanding. Religious spirit is an important reason for this research, which is researched using descriptive qualitative methods through observation of the role of religious leaders who are randomly selected in the phenomenological research area. In this study, it was found that there was a strong interaction between religious leaders and the community through messages to maintain mutual attitudes and speech was the key to establishing a harmonious relationship. The practice of different religious rituals for society is common. These differences are found at the level of branching, not in the main things such as tahlilan, syukuran, mapag sri, sedekah bumi, selametan and other religious rituals. It can be concluded that the role models of regigious figures are the main key to maintaining harmony in the life of religious communities. They provide direct demands on attitudes and actions in society. They educate the community which is internalized through actions on religious practices that are assimilated in customs, culture and rituals related to the needs of religious communities in rural communities and provide new knowledge for the community to maintain mutual religious harmony, side by side in diversity.